Kerjasama Jepang dan Indonesia di Bidang Ketenagakerjaan dalam Program Tokutei Ginou tahun 2019 - Tombalisa, Nur Fadhilla; Fathurahmi, Enny; Wirawan, Rendy (Department of International Relations, Universitas Mulawarman, 2022)
This study aims to analyze cooperation between Japan and Indonesia in the Tokutei Ginou program, as well as to describe the history of the formation of the employment program created by the Japanese government. The research method used is descriptive with secondary data types. The analysis technique used is qualitative. The concepts used are the National Interest and National Health Worker concept. The results of this shows that both Indonesia and Japan benefitted from Tokutei Ginou program such increasing Japanese workers’ welfare, creating opportunities for Indonesian specified skilled workers, maintaining smooth economic productivity for Japan and Indonesia, enchancing cooperative relations between Japan and Indonesia.